Performance improvement of visible light communication links based on coded unipolar OFDM - N. Al-Musawi, Wasnaa; K. Al-Musawi, Hassan (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Visible light communications are limited by the narrow bandwidth of their sources as the light-emitting diodes, which restricts the high data rates transmission. A potential technique such as multi-carrier modulation is considered promising for achieving a high-speed data rate and enhancing system performance. This paper proposes turbo coding with unipolar orthogonal frequency-division multiplexing (U-OFDM) for indoor environments. The system under U-OFDM considerations can reduce the inter-symbol interference caused by multiple paths and mitigate burst errors by adopting an iterative turbo decoding. The system performance is evaluated regarding the bit error rate (BER) for the range of the signal-to-noise ratio (SNR) under receiver field-of-view (FOV) restriction. The obtained results show that the performance system of the target BER (below the threshold limit of 3.8×10−3) has a power penalty of ~9 dB for modulation order of 64 for quadrature amplitude modulation scheme, FOV of 50°, and incidence angle of half power assigned to 30°. The obtained results also showed a ~10.8 dB improvement in the SNR when comparing the present system with coded-DC-biased optical OFDM under the same considerations.